Pendidikan Islam Lansia : Memotret Metode Pembelajaran di Pesantren Lansia Ahsanu ‘Amala - Zaki Zakaria; Diningrum Citraningsih; Rz. Ricky Satria Wiranata (Jurnal Kajian Pendidikan Islam, 2023)
This study aims to describe the method of Islamic education in the elderly pesantren ahsanu 'amala. This type of research is field research with qualitative methods. The objects in the study are Islamic boarding school leaders, teachers or teachers, and elderly students. Data collection techniques by means of interviews, observation, and documentation. Data analysis techniques by means of data reduction, data display and conclusion drawing. To test the validity of the data, credibility, transferability, dependability and confirmability tests are carried out. The results of research on Islamic education methods in the ahsanu 'amala elderly boarding school were carried out with 4 methods, namely reading and memorization methods, lecture methods, discussion methods, and natural tadabbur.